Electronic structures and half-metallicity of carbon doped bulk and surface CdS: The modified Becke-Johnson potential calculation. (January 2017) - Huang, X.N.; Fan, S.W.; Pan, L.Q.
Abstract: The electronic structures and ferromagnetism for bulk and surface CdS with CS defects are investigated by the full potential linearized augmented plane wave method together with the modified Becke-Johnson potential. Calculations show bulk and surface CdS with CS defects are half-metallic ferromagnet. Each CS defect could produce the total magnetic moment of 2.00 µB . Electronic structures indicate the stable ferromagnetism could be attributed to the p-d exchange-like p-p coupling mechanism. Sulfur vacancies would give rise to the magnetism vanishing. For the nonpolar ( 10 1 ¯ 0 ) surfaces, the CS defects prefer to occupy the surface layer sites. Highlights: The CS defects could induce the bulk and surface CdS to be typical half metallic ferromagnet. Electronic structures show ferromagnetism come from p-d exchange-like p-p coupling. Chemical pair interactions indicate CS tend to from the clustering distribution in CdS host. Sulfur vacancy would force the CdS with CS defect losing magnetism.